Intertextualidade nas crônicas de José Simão - Custódio, Fernando Elias (2010)
This dissertation inserts itself in the line of investigation Text and discourse in the modality oral and writing. It holds the theme intertextuality in the chronicles of José Simão. It boards the principal classification of intertextuality, utilized by the writer, to the construction of meaning of the text. It holds by principal objectives to contribute to the studies of report intertextuality which happens between the chronicles and the news published in the Newspaper, in the Internet and in the Television. The specify objectives are: 1. to verify the principal forms of intertextuality present in the chronicles of José Simão; 2. to examine in which conditions the intertextuality helps the process of reading of chronicles; 3. to verify the intertexts which dialogue with the chronicles of José Simão. The problem of reading of chronicles is in the absence of activate of the intertext in the moment of reading. In the dimension textual-discursive, it considers the report between the old‟ and the new‟ with value of subversion. The studied material includes chronicles of José Simão, published in the Folha de S. Paulo in the period of June, 02nd , 2009 to June, 25th, 2009. The accept procedure, in this investigation, is analytic-descriptive. The obtained results denote that: 1. the principal forms of intertextuality presents in the chronicles of Simão are: explicit, implicit, thematic, stylistic and intergeneric; 2. the intertextuality is indispensable, requiring a observant reader to the principal facts of daily; 3. the chronicles have a standard structure, fulfilled by various themes retired of the proper Newspaper, of the Internet and of Television. It concludes itself that the study of intertextuality is fundamental to the construction of meaning of the text, because the various produced texts form part of previous knowledge of the reader